2021
DOI: 10.3390/nano11071834
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Molecular Dynamics Simulation on the Anti-Adhesion Behavior of Alkanethiols on Nickel Insert in Micro Injection Molding

Abstract: Due to the adhesion between the polymer melt and nickel (Ni) mold insert in the micro injection molding process, deformation defects frequently occur when the microstructures are demolded from the insert. In this study, self-assembled alkanethiols were applied to modify the surface of Ni mold insert to reduce its surface energy. Experimental trials were undertaken to explore the effect of alkanethiols coating on the replication quality. After that, molecular dynamics (MD) simulation was then used to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Adhesion is the result of molecular or atomic forces between objects, causing them to bond closely [79]. This phenomenon involves various mechanisms of adhesion, among which van der Waals forces generate short-range attractions between molecules, including London dispersion forces and Debye polarization forces, creating temporary charge distributions and resulting in attraction [48,80,81]. Electrostatic forces, also known as Coulomb forces, arise from interactions between charges and can lead to attractions or repulsions between positively and negatively charged entities [82].…”
Section: Mechanism and Failure Modementioning
confidence: 99%
“…Adhesion is the result of molecular or atomic forces between objects, causing them to bond closely [79]. This phenomenon involves various mechanisms of adhesion, among which van der Waals forces generate short-range attractions between molecules, including London dispersion forces and Debye polarization forces, creating temporary charge distributions and resulting in attraction [48,80,81]. Electrostatic forces, also known as Coulomb forces, arise from interactions between charges and can lead to attractions or repulsions between positively and negatively charged entities [82].…”
Section: Mechanism and Failure Modementioning
confidence: 99%
“…Lucchetta et al 22 developed a multiscale model of submicron scale polymer flow and analyzed the sensitivity of the model to polymer material type, mold surface properties, and mold temperature, with a maximum error of 8% in the accuracy of the multiscale model. In our previous exploration, 23 we adopted a molecular dynamics approach to scrutinize the nano‐injection molding demolding process, identifying that minimizing the interfacial interaction between the mold insert and polymer molecular chains is essential for reducing demolding force. Xhou and Qiu 24 found that the surface morphology of the mold cavity determined the contact mode between the mold insert and the part, which affected the adhesion and friction during the demolding process.…”
Section: Introductionmentioning
confidence: 99%